(untitled) (New York, 1996)
Mosaic 2 is designed for college ESOL students who are at a high-intermediate to low-advanced level of proficiency. It aims to be both flexible and easy to use. The programme contains four separate, yet co-ordinated, texts: a grammar, a reader, a writing book and a listening/speaking book. New to the third edition is a fifth co-ordinated text - a video activities book. The texts in the MOSAIC 2 programme are filled with a variety of skill-building exercises, activities and practical information about life in the United States and Canada. This new edition features new design and a new theme for Chapter 8. Each of the texts in the series can be used by itself or in combination with any of the other books. The programme is designed so that themes, vocabulary and grammar structures are co-ordinated chapter by chapter across all five books. In this way, material in any given chapter of one book corresponds to, and reinforces, the material taught in that same chapter of any of the other texts. All of the books in the series focus on building skills, not just testing comprehension. Skills are introduced with clear instructions, practised with exercises and reinforced where appropriate. The wide range of exercises and activities, including interviews, role-plays and games, are communicative and personalized to encourage students to express themselves in English.
Keywords: English language,English language; Reading